Od Chrystusa historii i wiary do Jezusa wewnętrznego reformatora. Zmiana perspektywy chrystologicznej w myśli Tomasza Polaka - Artemiuk, Przemysław (Warszawskie Studia Teologiczne, 2024)
The aim of the article is to show the change that has taken place in prof. T. Pole to Jesus of Nazareth. Based on his works, the author attempted to recreate the transition from Christ of history and faith to Jesus, the inner reformer and a man with a deep experience of God. In the first part of the article, the author presented the image of the Nazarene that emerges from the writings of T. Węcławski. In the second part, an outline of his paschal ontology. The third part was devoted to the current views of the Poznań researcher, expressed primarily in the last book on the church system and in interviews accompanying its publication. The research conducted allows the following conclusions to be drawn: fundamental Christology, which emerges from T. Węcławski's works published until 2006, is methodologically organized, focused on key Gospel threads, and shows Jesus of history and faith; the outline of paschal ontology is an original concept attempting to characterize the revelation of God in Jesus Christ using new ontological and gnoseological principles; Jesus emerging from the "Church System" is a man of the religious order, but the possibility of clearly defining His historical person seems difficult.